MASS SPECTROSCOPIC AND THERMAL ANALYSIS OF FURFUROLIDENUREA (Scientific journal of the Fergana State University, 2022)
In this article, a compound based on urea and furfural was examined using mass spectrometry, which is one of the most accurate methods for determining substances. Based on the obtained values, the molecular masses of the resulting compound were determined. As a result of the thermal analysis of this compound, its melting temperature, temperature stability, and temperature-induced mass loss were determined.